The Effect of Tax Expense Efficiency, Debt to Equity Ratio and Firm Size on Return on Assets - Dina Kamila; Salza Adzri Arismutia (Ilomata International Journal of Tax and Accounting, 2026)
This study looks at the impact of Firm Size, Debt to Equity Ratio, and Tax Expense Efficiency on Return on Assets in coal subsector companies listed on the Indonesia Stock Exchange between 2017 and 2024. There are seven firms in the sample, which results in 56 firm-year observations. “Pooled ordinary least squares (OLS) regression is used in the empirical analysis on firm-year data, and diagnostic tests are used to confirm that the calculated connections are reliable”. The findings show that the regression model as a whole is statistically significant, indicating that the independent variables work together to explain changes in Return on Assets. However, partial test findings reveal that Firm Size has a positive and statistically significant impact on Return on Assets, the Debt to Equity Ratio has a negative and statistically significant association, and Tax Expense Efficiency has no statistically significant influence. These results suggest that business size and capital structure have a greater impact on profitability in the coal subsector than does tax expense efficiency. By offering sector-specific data from a capital-intensive industry, this study adds to the body of literature by emphasizing the significance of financing choices and operational scale in determining business profitability as well as the limited relevance of tax efficiency under stringent regulatory frameworks.